2021
DOI: 10.3390/molecules26040979
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity Evaluation of FlexirubinType Pigment from Chryseobacterium artocarpi CECT 8497 and Related Docking Study

Abstract: The current research is focused on studying the biological efficacy of flexirubin, a pigment extracted from Chryseobacterium artocarpi CECT 8497.Different methods such as DPPH, H2O2, NO•, O2•-, •OH, lipid peroxidation inhibition by FTC and TBA, ferric reducing and ferrous chelating activity were carried out to evaluate the antioxidant activity of flexirubin. Molecular docking was also carried out, seeking the molecular interactions of flexirubin and a standard antioxidant compound with SOD enzyme to figure out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Moreover, the results showed that highest ABTS + scavenging activity was obtained for BC samples functionalized with flexirubin-type pigment, at 38.96 ± 0.49% ( Figure 5 B). The antioxidant activity of the flexirubin-type pigment, which can be attributed to the hydrogen atom transfer from the phenol, has been previously determined through different assays, besides the radical scavenging activities, namely lipid peroxide inhibition and ferrous chelating ability [ 20 ], which support the significance of flexirubin-type pigment as a powerful antioxidant, relevant for a wide range of applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the results showed that highest ABTS + scavenging activity was obtained for BC samples functionalized with flexirubin-type pigment, at 38.96 ± 0.49% ( Figure 5 B). The antioxidant activity of the flexirubin-type pigment, which can be attributed to the hydrogen atom transfer from the phenol, has been previously determined through different assays, besides the radical scavenging activities, namely lipid peroxide inhibition and ferrous chelating ability [ 20 ], which support the significance of flexirubin-type pigment as a powerful antioxidant, relevant for a wide range of applications.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the yellow flexirubin-type pigment, which has been applied in the treatment of chronic skin disease, eczema, and gastric ulcers, also displays a wide range of pharmacological effects, which includes a high antioxidant potential [ 19 , 20 ]. In this study, the flexirubin-type pigment used was produced by Chryseobacterium shigense isolated from lactic acid beverage [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting point, is that on the plant-bacteria interaction model, flexirubin also performs as free radical scavenging antioxidant protecting from the attack of free radicals ( Combes and Finet, 1997 ; Schöner et al, 2015 ). The antioxidant potential via hydrogen donating ability of flexirubin has been shown through the assessment using different assays such as radical scavenging activities, lipid peroxide inhibition and ferrous chelating ability ( Mogadem et al, 2021 ). Several studies show that microalgae produce reactive oxygen species (ROS) to get an advantage in the competition for resources against other algae, be a way to prevent fouling bacteria, and act as a signalling mechanism between cells ( Marshall et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Flexirubin which are widely distributed in the genus Flavobacterium . They are pigments that form a yellow colony and are composed of a 2–5 dialkylresorcinol (DAR) with a non-isoprenoid aryl-polyene carboxylic acid ester [ 38 , 39 ]. Although their ecological roles are unknown, DAR compounds are known to have antibacterial properties in Pseudomonas sp.…”
Section: Resultsmentioning
confidence: 99%